(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Conservative treatment of macular edema associated with retinal vein occlusion is often unable to control progression of the disease. ME chronization is observed in ?30% patients, excludes spontaneous resolution, is difficult to treat and is considered a cause of decreased visual acuity (VA). A pathomorphological picture is very variable: there are both rich and poor pathologic semiology of the eye fundus. Despite the long history of studying, this variability and its connection with VA are understudied, which increases the treatment uncertainty. The time terms and sequence of therapeutic actions, medication doses, retinal laser coagulation (LC) modes, a number of repeated interventions, long-term outcomes of the treatment are objects of multi-center randomized investigations and a subject of discussion today. One of the ways to improve the treatment of persisting ME is a search for clear criteria for patients’ differentiation and to perform treatment in regard to the state of a certain patient. This differentiating approach refers to a precise detection of ME using maximum information that can be provided by traditional and brand new examination methods. Purpose. To assess the variety of pathologic semiology of the ocular fundus in patients with macular edema associated with retinal vein occlusion who were resistant to conservative treatment. Material and Methods. 160 patients, of a total of 377 patients with RVO-associated ME, who were resistant to conservative treatment were observed. The patients underwent the course of conservative treatment (which was not a success) at Eye Microsurgery Centre, Kyiv, within 2009-2012; they were not performed laser coagulation (LG) of the retina; they had no other macular disorders; the optic media of the eye were transparent and artery hypertension was compensated. There were 77 men and 83 women, aged, on average, 60.7±9.2 and 62.7±11.1, respectively. The CT course was performed twice with a one-month interval and included topical and systemic vasodilators, fibrinolytics, vasoprotectives and corticosteroids. At admission to the clinic with recommendation to continue treatment using laser therapy, medical history of a patient was taken, complaints were recorded and standard general and ophthalmic examination was performed. Results. In cohort of RVO-associated ME patients resistant to conservative treatment, a great variability of the parameters studied was observed: VA, 0.01-1.0; LSCR, 2-27 dB; scotoma rates, 2-20?; IOP, 11- 28 mmHg; ME thickness in the center, 249-877 µm; ME thickness in the parafovea, 228-693 µm; inner NR layer thickness, 92-605 µm; outer NR layer, 110-714 µm. Patients’ distribution was unimodal in regard of NR inner layer thickness; however, as for NR outer layer thickness, the whole cohort was divided into two subgroups with local modes of 205 и 385 µm (320 µm section). The variations of the ME thickness can explain only ? 11% of VA variations. Conclusion. Pathomorphological picture of the disease varies a lot in ME associated with retinal vein occlusion that was resistant to concervative treatment. Significant heterogeneity of the cohort studied and differences in mutual correlation of the pathological symptoms point to the possibility of objective classification of the disease according to the pathologic symptomatology complex.